Composite Dietary Antioxidant Index and Plasma Levels of Soluble Klotho: Insights from NHANES. (7th February 2023) - He, Huiqin; Chen, Xin; Miao, Da; Zhang, Hongxia; Wang, Yu; He, Xingkang; Chen, Xiaoli; Dai, Ning
Abstract : Objectives . The association between dietary antioxidants and soluble Klotho (S-Klotho) levels remains unknown. We investigated to explore whether the composite dietary antioxidant index (CDAI) was associated with serum levels of S-Klotho in the middle-aged population. Methods . Eligible participants were identified from the National Health and Nutrition Examination Surveys (NHANES) from 2007 until 2016. The CDAI was calculated from the intake of six dietary antioxidants. The serum levels of S-Klotho were measured via enzyme-linked immunosorbent assay (ELISA). Generalized linear and nonlinear models were established to analyze the relationship between CDAI and S-Klotho levels. Results . Based on the S-Klotho quartiles, S-Klotho levels were higher in young women, Blacks, higher education, never smokers, lower waistlines, no medication use, and those with higher CDAI. Univariate analysis revealed that age, gender, race, smoking status, body mass index, waistline, and medication use were associated with serum levels of S-Klotho. When potential confounders were controlled, CDAI was significantly associated with S-Klotho levels. Subgroup analysis also revealed that this association remained significant in individuals who had the highest quartiles of CDAI, aged population (>60 years), male, and never smoker. A nonlinear relationship was observed between the CDAI and S-Klotho plasma concentrations. Conclusion . CDAI was positively correlated with plasma levels of S-Klotho after controlling for covariates. Further studies are needed to validate the current findings and explore the fundamental mechanisms.